Simulated microgravity suppresses MAPK pathway‐mediated innate immune response to bacterial infection and induces gut microbiota dysbiosis. Issue 11 (12th September 2020) - Wang, Jing; Han, Conghui; Lu, Zhe; Ge, Pupu; Cui, Yu; Zhao, Dongdong; Yang, Xi; Wu, Bo; Qiang, Lihua; Zhang, Yong; Chai, Qiyao; Lei, Zehui; et al.
Abstract: During spaceflight, astronauts are subjected to various physical stressors including microgravity, which could cause immune dysfunction and thus potentially predispose astronauts to infections and illness. However, the mechanisms by which microgravity affects innate immunity remain largely unclear. In this study, we conducted RNA‐sequencing analysis to show that simulated microgravity (SMG) suppresses the production of inflammatory cytokines including tumor necrosis factor (TNF) and interleukin‐6 (IL‐6) as well as the activation of the innate immune signaling pathways including the p38 mitogen‐activated protein kinase (MAPK) and the Erk1/2 MAPK pathways in the Enteropathogenic escherichia coli (EPEC)‐infected macrophage cells. We then adopted hindlimb‐unloading (HU) mice, a model mimicking the microgravity of a spaceflight environment, to demonstrate that microgravity suppresses proinflammatory cytokine‐mediated intestinal immunity to Citrobacter rodentium infection and induces the disturbance of gut microbiota, both of which phenotypes could be largely corrected by the introduction of VSL#3, a high‐concentration probiotic preparation of eight live freeze‐dried bacterial species. Taken together, our study provides new insights into microgravity‐mediated innate immune suppression and intestinal microbiota disturbance, and suggests that probiotic VSL#3 has great potential as a dietary supplement in protecting individuals from spaceflight mission‐associated infections and gut microbiota dysbiosis.